Penentuan Kadar Glukosa Urine di Laboratorium Rumah Sakit Sari Mutiara Medan - Fitri Dian Puspa Nadeak; Riyanto riyanto; Rosliana Lubis (Universitas Medan Area, 2019)
The purpose of this study was to determine urine glucose level in patients who came to the Sari Mutiara General Hospital in Medan. Research method with qualitative and quantitative test, qualitative analysis of urine glucose by inserting urine sample 5 - 8 drops into reaction tube that already contains 5ml of benedict solution, then burned on fire and observe the color change that occurs, quantitative analysis of urine glucose by adding sodium carbonate and 2 rounds of boiling stone into a reaction tube containing 5 ml of benedict solution, burned over a flame, then drop urine using a 1 ml pipette, while dripping urine, the liquid should not stop boiling, the titration ends when the blue is not look again.The results of qualitative and quantitative analysis were obtained from 25 test samples, 15 positive urine glucose patients, and 10 negative urine glucose patients.